A mobile phone malicious software detection model with behavior checker - Yap, TS; Ewe, HT (2005)
There have been cases reported for the new threats from mobile phone technologies and it has raised the awareness among the technology and antivirus vendors. Malicious programs such as Viruses, Trojan, and Worms have been created and targeted at mobile phone. This paper discusses the possible attacking model on mobile phone adapted from malicious attack on computer. It also presents the types of attack and appropriate solution model for mobile phone. A prototype of the simulation of malicious software and detection software on mobile devices is developed and the results of applying this approach to simulated malicious software and detection software on mobile device are also presented,